EFEKTIFIVITAS PEMBELAJARAN IPA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS - Debi Hardian Saputra; Ermila Mahariyanti; Irwansah Irwansah (JURNAL ASIMILASI PENDIDIKAN, 2024)
This research is aimed to determine the effectiveness of science learning using the problem-based learning model on the critical thinking skills of class VII A students at Sullamul Mubtadi Anjani Islamic Middle School. This research is a qualitative research using data collection methods including tests, observations, interviews and documentation. Data validity uses triangulation techniques, extends participation, and increases persistence. While the data analysis technique uses the Analysis Interactive model from Miles and Huberman including data collection, data reduction, data presentation and conclusions or data verification. The results of the study show that through science learning by using the problem based learning model, it can improve students' critical thinking skills. It can be seen from the results of the critical thinking ability test that all students get results in the category of high-ability students. The results of interviews with teachers revealed that the science learning model using the problem-based learning model could improve students' critical thinking skills and the results of interviews students liked science learning using the problem-based learning model and could improve students' critical thinking skills according to the results of the overall interview. towards teachers and students. Then the results of the observation of activity showed that students in class VII A were active in learning according to the assessment of each indicator made by the researcher.